TAp63α Is Involved in Tobacco Smoke-Induced Lung Cancer EMT and the Anti-cancer Activity of Curcumin via miR-19 Transcriptional Suppression - Xie, Chunfeng; Zhu, Jianyun; Yang, Xue; Huang, Cong; Zhou, Liping; Meng, Zili; Li, Xiaoting; Zhong, Caiyun (Frontiers in Cell and Developmental Biology, 2021)
As a key risk factor for lung cancer, tobacco smoke (TS) influences several cellular processes, including epithelial-mesenchymal transition (EMT). TAp63α is a crucial transcription factor involved in tumor progression. The present study was designed to investigate the potential role and underlying mechanisms of TAp63α in TS-induced lung cancer EMT. We found that compared to normal tissues, the tumor tissues collected from lung cancer patients showed a lower level of TAp63α expression, along with downregulated E-cadherin expression and upregulated Vimentin expression. Results of treatment with TAp63α and TAp63α siRNA as well as with tumor growth factor-β (TGF-β) showed that TAp63α acted as a tumor suppressor gene, and its upregulated expression suppressed lung cancer EMT. Significantly, TS exposure altered expression of EMT-related markers, enhanced cell migratory and invasive capacities, and decreased the TAp63α expression level in lung cancer cells. Overexpression of TAp63α significantly alleviated TS-stimulated lung cancer EMT. Mechanistically, TAp63α expression transcriptionally reduced the miR-19 level, which resulted in the suppression of lung cancer EMT. Additionally, as a natural compound possessing anti-cancer effects, curcumin inhibited TS-induced lung cancer EMT by increasing TAp63α expression and reducing miR-19 expression. Collectively, our results indicate that TAp63α inhibits TS-induced lung cancer EMT via transcriptionally suppressing miR-19 and the inhibitory effect of TAp63α on miR-19 mediates the anti-cancer action of curcumin. These findings provide new insights into novel targets for lung cancer prevention.